3D Computer Vision Efficient Methods and Applications - Wöhler, Christian (X.media.publishing, 2009)
This book provides an introduction to the foundations of three-dimensional computer vision and describes recent contributions to the field. Geometric methods include linear and bundle adjustment based approaches to scene reconstruction and camera calibration, stereo vision, point cloud segmentation, and pose estimation of rigid, articulated, and flexible objects. Photometric techniques evaluate the intensity distribution in the image to infer three-dimensional scene structure, while real-aperture approaches exploit the behavior of the point spread function. It is shown how the integration of several methods increases reconstruction accuracy and robustness. Applications scenarios include industrial quality inspection, metrology, human-robot-interaction, and remote sensing.